Envisioning the Future of Mining (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
To date, many challenges have been faced in the production of mineral raw materials to provide necessary supplies in almost any production chain. In addition to the traditional search for more efficient processes, cleaner and safer operations, and higher levels of social acceptance, there is a need for the mining industry to become a major actor in circular economy, decarbonization, and digital transformation processes. This reprint includes the articles published in the Special Issue of Mining entitled "Envisioning the Future of Mining".